Физическая культура и развитие здоровья ребенка дошкольного возраста: Физическая культура и развитие здоровья ребенка дошкольного возраста - Абдукаримов, Нурмахан (Физическое воспитание, спорт и здоровье, 2025)
Physical education is the most important means of introducing each person to physical culture and sports, as well as the most important component of the system of human education in society. In a preschool educational organization, physical education is aimed at the timely formation of motor skills and abilities of preschool children. The main content of this work is based on various options for walking, running, jumping, climbing, throwing, some types of sports exercises, sports games, general developmental exercises, elements of acrobatics and rhythmic gymnastics, outdoor games. In the life of each person, his development, health, personality development, preschool age is of great importance. A comprehensive education of a child during these years has a special influence on his future, school education and personality development. Physical education during these years is the main